CRYOADAPTATION OF BOWEL SEGMENTS DURING THE APPLICATION OF ANASTOMOSIS IN PATIENTS WITH ACUTE INTESTINAL OBSTRUCTION OF TUMOR GENESIS - Ksonz, I.V.; Harchenko, D.A.; Ksonz, V.I. (World of Medicine and Biology, 2019)
The frequency of the large intestine intestinal obstruction (IO), caused by tumor genesis, ranges from 60 to 80% of all clinical conditions. The problem of restoring the continuity of the large intestine after resection in the case of obstruction, caused by the tumor process, remains relevant and multifactorial and has a high social significance. Patients suffering from stoma usually refuse reconstructive interventions, and the presence of stomas significantly reduces the quality of life and social adaptability of this group of patients. An important technical task in the correction of IO, is the formation of a reliable intestinal anastomosis with a pronounced segregation difference. The problem of the intestine rehabilitation is one of the most complicated in modern abdominal reconstruction and plastic surgery. Despite the improvement of the intestinal septum techniques, the use of new biologically inert and atraumatic suture materials, mechanical seams, various methods of strengthening and sealing anastomosis, the incidence of intestinal sutures is 1.6 - 28.4%. Postoperative lethality remains fairly high and reaches 23.8%. Complicated situations for a surgeon arise when necessary by joining intestinal departments that function and one that is excluded from digestion. Many domestic surgeons prefer the stage-by-stage treatment of clinical trials: intestinal stools or unloading "T-shaped" anastomoses. However, some surgeons consider the formation of an initial adapted anastomosis to be a choice operation, arguing that there is no hydrodynamic overload along the suture line, with the risk of their failure, for any difference in the diameters of the segments, as well as the earlier term of restoration of the peristalsis and the possibility of adequate enteral nutrition. The results of surgical treatment of 65 patients with colon tumors with the phenomena of decompensated intestinal obstruction clinical manifestations have analyzed. Contingent of patients: women - 29, men - 36. The average age is 65.2 years, the age varies from 46 to 87 years. Radically operated with resection of the tumor R0 of 20 men, including primary reconstructive surgery performed in 13 patients. Different types of colostomy were performed in 21 patients, including after resection of the tumor in 7. Among women, radically operated 17. Primary-recovery operations in 12, colostomy after tumor resection imposed in 6. With the help of cold adaptation, we restored the intestinal continuity in 18 patients. We did not observe the anastomosis or the anastomositis phenomena. In addition, the active reduction of the driving loop under the influence of cold is a peculiar test for the restoration of the motility of the stomach ulcer. An unsuccessful attempt to reduce the diameter was noted in 2 patients, who were imposed single-stranded colostomy. The reasons that the intestine did not react to the cold, we are not known. Perhaps this is due to decompensation of mechanisms of rapid contractile ability of the intestine.